Myelin-induced inhibition in a spiral ganglion organ culture: approaching a natural environment in vitro - Kramer, Benedikt (Neuroscience, 2017)
The performance of a cochlear implant depends on the defined interaction between afferent neurons of the spiral ganglion and the inserted electrode. Neurite outgrowth can be induced by neurotrophins such as brain-derived neurotrophic factor (BDNF) via tropomyosin kinase receptor B (TrkB). However, neurotrophin signaling through the p75 neurotrophin receptor (p75) inhibits neurite outgrowth in the presence of myelin. Organotypic cultures derived from postnatal (P3-5) mice were used to study myelin-induced inhibition in the cochlear spiral ganglion. Neurite outgrowth was analyzed and quantified utilizing an adapted Sholl analysis. Stimulation of neurite outgrowth was quantified after application of BDNF, the selective TrkB agonist 7,8-dihydroxyflavone (7,8-DHF) and a selective inhibitor of the Rho-associated kinase (Y27632), which inhibits the p75 pathway. Myelin-induced inhibition was assessed by application of myelin-associated glycoprotein (MAG-Fc) to stimulate the inhibitory p75 pathway. Inhibition of neurite outgrowth was achieved by the selective TrkB inhibitor K252a. Stimulation of neurite outgrowth was observed after treatment with BDNF, 7,8 DHF and a combination of BDNF and Y27632. The 7,8-DHF-induced growth effects could be inhibited by K252a. Furthermore, inhibition of neurite outgrowth was observed after supplementation with MAG-Fc. Myelin-induced inhibition could be overcome by 7,8-DHF and the combination of BDNF and Y27632. In this study, myelin-induced inhibition of neurite outgrowth was established in a spiral ganglion model. We reveal that 7,8-DHF is a viable novel compound for the stimulation of neurite outgrowth in a myelin-induced inhibitory environment. The combination of TrkB stimulation and ROCK inhibition can be used to overcome myelin inhibition.
Gesehen am 06.07.2018
Available online 14 June 2017